27th Congress of SCTM - Jadranka Blaževska Gilev (Macedonian Journal of Chemistry and Chemical Engineering)
The 27th Congress of SCTM organized by the Society of Chemists and Technologists of Macedonia took place in Ohrid, Macedonia, September 25th – 28th, 2024. With 4 plenary sessions, 9 invited lecturers from Italy, Spain, Serbia, Czech Republic, Denmark, and the United Kingdom and almost 200 presentations by 550 authors and co-authors from the region and much beyond, it made it a truly international congress, where a diverse array of topics were presented, which reflect the great energy and commitment of the scientific community. From discoveries in nanomaterials, to advances in biotechnology, electrochemistry, green chemistry to the latest pharmaceutical research, each abstract demonstrates the extraordinary flexibility and ingenuity of our colleagues. It is particularly important to mention the wide range of oral and poster presentations by researchers representing Austria, Azerbaijan, Bosnia and Herzegovina, Bulgaria, Croatia, Germany, Greece, Italy, Kosovo, Montenegro, Poland, Serbia, Slovenia, Spain, Romania and Russia.